Effect of the Connecting People Intervention on Social Capital: A Pilot Study. (July 2019) - Webber, Martin; Morris, David; Howarth, Sharon; Fendt-Newlin, Meredith; Treacy, Samantha; McCrone, Paul
Objective: This pilot study evaluated the effect of the Connecting People Intervention (CPI) on access to social capital, social inclusion, and mental well-being. Method: A prospective one-group pretest – posttest preexperimental study of 155 people with a mental health problem or a learning disability receiving care and support from health and social care practitioners trained in the CPI was used. Results: Participants exposed to practice with high fidelity to the CPI model had significantly higher access to social capital ( p = .03, partial η 2 = .05) and perceived social inclusion ( p = .01, partial η 2 = .07), and lower service costs (−£1, 331, 95% confidence interval = [−£69, −£2593]), posttest than those exposed to low fidelity to the model. All participants had significantly higher mental well-being posttest ( p < .001). Conclusions: These preliminary results suggest that when fully implemented, the CPI can improve social outcomes for people with a mental health problem or learning disability.